MOTIVASI GURU MENGHADAPI ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH DASAR - Miranda Celia Putri; Dini Apriliani; Opi Andriani (JURNAL ILMIAH RESEARCH STUDENT, 2024)
The aim of this research is to determine teacher motivation in dealing with children with special needs, especially in elementary schools. The method used in this research is a literature review study or literature review. Literature study is a research design used to collect data sources related to a topic found in the field. Data collection for literature studies was carried out using the Google Scholar search tool. The appropriate and required screening results contained 10 National Journal articles based on the articles found and analyzed. The result of this research is that we found a way to raise the enthusiasm of teachers in dealing with and creating inclusive education in schools, such as teachers becoming demonstrators, motivators, mediators, facilitators and evaluators in the child's learning process.